A rapid-response ultrasensitive biosensor for influenza virus detection using antibody modified boron-doped diamond - Nidzworski, Dawid (Sci Rep, 2017)
According to the World Health Organization (WHO), almost 2 billion people each year are infected worldwide with flu-like pathogens including influenza. This is a contagious disease caused by viruses belonging to the family Orthomyxoviridae. Employee absenteeism caused by flu infection costs hundreds of millions of dollars every year. To successfully treat influenza virus infections, detection of the virus during the initial development phase of the infection is critical, when tens to hundreds of virus-associated molecules are present in the patient’s pharynx. In this study, we describe a novel universal diamond biosensor, which enables the specific detection of the virus at ultralow concentrations, even before any clinical symptoms arise. A diamond electrode is surface-functionalized with polyclonal anti-M1 antibodies, which then serve to identify the universal biomarker for the influenza virus, M1 protein. The absorption of the M1 protein onto anti-M1 sites of the electrode change its electrochemical impedance spectra. We achieved a limit of detection of 1 fg/ml in saliva buffer for the M1 biomarker, which corresponds to 5–10 viruses per sample in 5 minutes. Furthermore, the universality of the assay was confirmed by analyzing different strains of influenza A virus.